2022
DOI: 10.1001/jamaophthalmol.2022.0055
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Cost-Related Barriers to Medication Adherence Among Patients With Glaucoma Enrolled in the National Institutes of Health All of Us Research Program

Abstract: IMPORTANCE Ability to afford medication is a major determinate of medication adherence among patients.OBJECTIVE To determine cost-related barriers to medication adherence by race and ethnicity in a nationwide cohort of patients with glaucoma. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study included patients with glaucoma enrolled in the National Institutes of Health All of Us Research Program, a nationwide longitudinal cohort of US adults, with more than 300 000 currently enrolled. Individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 39 publications
(71 reference statements)
1
38
0
Order By: Relevance
“…17 African American and Hispanic glaucoma patients have been shown to have more cost-related barriers to obtaining their medications, which may confer worse medication adherence and glaucoma outcomes. 18 In addition, anatomical differences by race, such as larger optic disks with less reserve axons and thinner corneas leading to an underestimation of intraocular pressure on applanation among those of African descent, are thought to play a role. 19,20 Glaucoma patients in this cohort differed on several key measures of socioeconomic status, including education, employment, and home ownership.…”
Section: Discussionmentioning
confidence: 99%
“…17 African American and Hispanic glaucoma patients have been shown to have more cost-related barriers to obtaining their medications, which may confer worse medication adherence and glaucoma outcomes. 18 In addition, anatomical differences by race, such as larger optic disks with less reserve axons and thinner corneas leading to an underestimation of intraocular pressure on applanation among those of African descent, are thought to play a role. 19,20 Glaucoma patients in this cohort differed on several key measures of socioeconomic status, including education, employment, and home ownership.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, and interaction between age and sex were associated with the prescription dose ( Table 3 ). In the USA, of 3826 patients with glaucoma selected from the nationwide longitudinal cohort, the median age group was 60–75 years, and 60.3% were women [ 14 ]. In the USA from 2004 to 2009, the proportion of the population with ocular hypotensive treatment was 11.5% while was 1.2% in 50–64 year, thus the proportion suddenly increased in the 65–79 years group and older [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their essential findings were as follows: (1) individuals who self-reported African American race and Hispanic ethnicity were more likely to report prescribed medications to be unaffordable compared with individuals of other races and ethnicities and (2) individuals who self-reported non-Hispanic White race were as likely as individuals of other races and ethnicities to request lower-cost medications. The authors concluded that among individuals of non-Hispanic African American race and Hispanic ethnicity, there were higher odds of self-reported difficulty affording medications compared with individuals of other races and ethnicities . Although it is not the purpose of this commentary to critique the article, there are a few points to underscore before providing a context for considering the salient points raised by the authors.…”
mentioning
confidence: 95%
“…In their article entitled “Racial and Ethnic Disparities in Cost-Related Barriers to Medication Adherence Among Patients With Glaucoma Enrolled in the National Institutes of Health All of Us Research Program,” Delavar et al analyzed responses regarding medication adherence in 3826 people with a diagnosis of glaucoma of the 350 000 individuals who participated in the National Institutes of Health All of Us database. These responses were associated with self-reported demographic characteristics.…”
mentioning
confidence: 99%